PERAN BUDAYA SEKOLAH DALAM MEMBANGUN KARAKTER RELIGIUS SISWA DI SEKOLAH DASAR ISLAM TERPADU (SDIT) LUKMANUL HAKIM LIMBOTO, KABUPATEN GORONTALO - Lahmudin, Siti Khairunnisa; Pomalingo, Samsi; Katili, Sukri (SINERGI : Jurnal Riset Ilmiah, 2025)
This study analyzes the role of school culture in building students' religious character at the Integrated Islamic Elementary School (SDIT) Lukmanul Hakim Limboto, Gorontalo Regency, and the values, traditions, and activities implemented at SDIT Lukmanul Hakim Limboto that support the formation of students' religious character. Through an ethnographic approach, this study collected data through observation, interviews, and documentation. The results of the study indicate that worship activities such as congregational prayer, tilawah, and Islamic Personal Development (BPI) learning serve as a foundation in instilling religious values. In addition, parental involvement is very important in supporting the process of educating children's religious character. The school also holds religious programs and social activities that involve students, creating a sense of concern for the community. Although challenges such as the influence of social media arise, the school is committed to educating students about the wise use of technology. This study concludes that school culture not only functions as a guideline for behavior, but also forms students' religious and social identities. Thus, SDIT Lukmanul Hakim plays an important role in creating a generation that has a strong character and is ready to face challenges in a diverse society.